BRAC University new campus development project construction schedule (October, 2019- December, 2019) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence BRAC University new campus development project construction schedule (October, 2019- December, 2019).